2012
DOI: 10.1007/s00167-011-1866-5
|View full text |Cite
|
Sign up to set email alerts
|

What does it take to have a high-grade pivot shift?

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 41 publications
4
114
2
8
Order By: Relevance
“…For the higher frequency of lateral meniscal lesions in the high-slope group, we support the assumption of Tanaka et al [38], presuming that steeper slope on the lateral tibial plateau and missing stabilization due to ACL insufficiency can lead to a high-grade pivot shift maneuver using the medial tibial plateau as a pivot point, forcing more stress on the lateral compartment of the knee. It might, therefore, be responsible for higher force transmission onto the lateral meniscus with consecutive higher number of lateral meniscal lesion in the acute ACL-insufficient knee with high LPTS.…”
Section: Discussionsupporting
confidence: 87%
“…For the higher frequency of lateral meniscal lesions in the high-slope group, we support the assumption of Tanaka et al [38], presuming that steeper slope on the lateral tibial plateau and missing stabilization due to ACL insufficiency can lead to a high-grade pivot shift maneuver using the medial tibial plateau as a pivot point, forcing more stress on the lateral compartment of the knee. It might, therefore, be responsible for higher force transmission onto the lateral meniscus with consecutive higher number of lateral meniscal lesion in the acute ACL-insufficient knee with high LPTS.…”
Section: Discussionsupporting
confidence: 87%
“…9,39,52 Therefore, in case of ACL-deficient knee and severe pivot shift, injury or relaxation of secondary restraints should be considered and their repair or reconstruction biomechanically justified to better control internal rotation and pivot shift phenomenon, as previously reported and recently confirmed by biomechanical studies. 9,[52][53][54] Extra-articular reconstruction, being peripheral to the center of rotation of the knee, has a longer lever arm for controlling rotation, which is far greater than that provided by a central intra-articular reconstruction. For this reason, although intra-articular reconstruction with hamstrings is a popular and effective procedure, leading to satisfactory results in more than 80% of cases, 55 attempts to improve these results and to better restore kinematics and function by addressing the extra-articular structures that contribute to the pivot shift phenomenon should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaka et al reviewed the literature on high-grade pivot shift and concluded that this results from a combination of ACL injury and disruption of the anterolateral capsule and/or lateral meniscus [9]. Musahl et al found both anterolateral ligament complex injuries and meniscal injuries to be associated with increased rotational instability on clinical testing [12] and Van Dyck et al found ALL injury to be associated with lateral meniscal injury [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the assumption that the majority of ACL ruptures occur with a similar combination of knee valgus and internal rotation of the tibia, injury to this relatively thin capsular structure seems likely in most cases. If this is the case, injury to the ALL may give rise to the abnormal rotation (and positive clinical pivot-shift) seen in cases of ACL injury [9][10][11][12][13]. Furthermore, it may be the failure to identify injury to the ALL that may result in the persistent instability exhibited by a subgroup of patients following ACL reconstruction [9,14].…”
Section: Introductionmentioning
confidence: 99%